STUDI KESESUAIAN LAHAN TERHADAP SUKUN (Artocarpus sp.) DI KOTA TARAKAN, KALIMANTAN UTARA - Ari Raharjo; Tety Elida; Djoko Prajitno (JURNAL AGRIBISNIS TERPADU, 2020)
North Kalimantan became a province in 2012. This relatively newly established province experienced a shortage of rice supply of 28.79 thousand tons / year. To overcome this, the Provincial Government of North Kalimantan brought rice from other provinces and carried out a diversification program for food sources of carbohydrates, namely breadfruit. Breadfruit production in the province reached 167.00 tons but the level of production of these plants in the city of Tarakan has decreased since 2013. This study aims to analyze the suitability of land to the growth of breadfruit plants in Tarakan City. The study was conducted in February 2019 in Juata Kerikil Village, Tarakan Utara District, Tarakan City, North Kalimantan Province. The research method was carried out by the field survey method by taking 2 soil samples and laboratory analysis. Observation of the sample is carried out at the top and bottom of soil layers. The parameter measured is the land suitability parameter. The results of the analysis show that the soil in the city of Tarakan is unsuitable land (N) with the soil texture and soil depth limiting factors.